Faktor Menonton Drama Korea Melalui Media Online (Web) Pada Remaja Putri - Talitha Reyhan Widana; Diajeng Herika Hermanu (Jayapangus Press, 2021)
This study aims to identify the factors of watching Korean dramas through online media (web) in young women. The study was conducted by distributing 400 questionnaires to young women in DKI Jakarta through an online survey. Quantitative data analysis methods are used and analyzed through factor analysis. The factor analysis summarizes two factors of watching Korean dramas, namely the learning factor and the sociability factor. It was found that Learning and Sociability are factors that influence young women to watch Korean dramas through online media (web) be-cause of the easy internet access and complete streaming facilities.